DAMPAK TEKNOLOGI INFORMASI TERHADAP SISWA DI SMA NEGERI 1 MANADO - Mewengkang, Norma (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: The Internet is one of the information technology where the internet is a very fun vehicle to learnand play. The phenomenon that occurs in senior high school (SMA) Negeri 1 Manado students who onaverage always use the internet either at home or internet cafes (Warnet) in allegedly using the internet andaccessing information without being filtered whether it can be consumption for use by students such assensual images or everything something that does not need to be known as a student, so it is suspected tohave a positive or negative impact for studentsIn this study researchers used a qualitative approach with Descriptive method. Descriptive method is used todescribe the situation and events under study by describing and exposing objects at the same time based onfacts. the number of samples was 95 students and the sampling technique was a simple Sample and randomStrati fi ed technique.The results showed that the importance of Internet messages for users where the messages are current oractual, interesting presentation, and easy to understand messages from the Internet because the language isinteresting, brief and clear. The Internet can increase knowledge and then change in behavior in the sense ofincreasing insight and get more friends both within the country or abroad, further messages via the Internetcan be trusted is the science but lack of confidence in the messages from the internet on gossip-gossipcelebrities. The advantages or advantages of using the internet is to get news from around the world, thenScience and technology and the increase of friends both domestically and abroad.Keywords: Information Technology, Internet